2021
DOI: 10.1155/2021/5549971
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of Multislice Spiral CT Cardiothoracic Combined with Angiography in Acute Chest Pain

Abstract: Acute chest pain is a common clinical emergency condition with a variety of causes, including acute coronary syndrome, pulmonary embolism, aortic coarctation, and pneumothorax. It is essential for emergency physicians to quickly and accurately understand the cause of acute chest pain. 64-slice spiral CT combined cardiothoracic angiography is an accurate and rapid way to diagnose and differentiate the cause of acute chest pain. 64-slice combined cardiothoracic angiography can accurately and rapidly display the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The most dangerous and deadly form of CHD is acute coronary syndrome (ACS) [ 2 ]. ACS is a series of clinical syndromes caused by rupture or erosion of atherosclerotic plaques, resulting in narrowing or occlusion of the coronary artery lumen, causing acute ischemia or necrosis of the myocardium [ 3 ]. ACS has a poor prognosis and a high mortality rate among cardiology diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The most dangerous and deadly form of CHD is acute coronary syndrome (ACS) [ 2 ]. ACS is a series of clinical syndromes caused by rupture or erosion of atherosclerotic plaques, resulting in narrowing or occlusion of the coronary artery lumen, causing acute ischemia or necrosis of the myocardium [ 3 ]. ACS has a poor prognosis and a high mortality rate among cardiology diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%